Strengthening International Legal/Institutional Response Towards Tackling Transborder Movement of Hazardous Wastes and Environmental Injustice in Africa: Nigeria in Focus - James Nkum, King; Beida, Julius Onivehu (Fakultas Hukum Universitas Lampung, 2024)
This paper discusses the importance of hazardous waste management in Africa, due to high importation of scrap computers and electronic devices. Improper waste management can lead to public health hazards like birth deficiencies, cancers, and infectious diseases. International environmental law's main function is not just to protect and preserve nature and the environment, but to manage waste on a global scale. The Basel Convention was established in the early 1990s seeks to address trans-boundary waste movements, focusing on hazardous waste. However, the trans-boundary movement of all waste, not just hazardous waste, remains a societal challenge globally. This paper critically analyzes the Bamako Convention, highlighting research trends, policy coherence, and sustainability implications. Using the doctrinal or library based research method, the paper found that recent incidents involving the trans-boundary movement of hazardous wastes on the African continent highlight the inadequacies and ineffectiveness of international law in solving this problem. The Bamako Convention's shortcomings are conspicuous, and the ban on trans-boundary movement of hazardous wastes is only one dimension of the bigger problem faced by African countries. The paper therefore recommends additional measures, such as strong laws and policies, mass education, virile civil society, source reduction, recycling, and landfill options. The paper also emphasizes the need for wealth creation, economic sustainability, and energy recovery in hazardous waste management.